Factors Associated with Cognitive Decline Among Patients with Non-Hemorrhagic Stroke - Hety Estora; Hendra Kusumajaya; Rima Berti Anggraini (Genius Journal, 2027)
Introduction : Cognitive decline is one of the long-term complications commonly found in patients with non-hemorrhagic stroke. This condition can affect the patient’s quality of life, ability to perform daily activities, and overall recovery process. Several risk factors such as advanced age, gender, family history of stroke, hypertension, history of cardiovascular disease, and smoking habits are suspected to contribute to this disorder. Objective: This study aims to determine the factors associated with cognitive decline in patients with non-hemorrhagic stroke at Depati Hamzah General Hospital Pangkalpinang in 2025 Method: This research employed an analytic observational design with a cross-sectional approach. A total of 74 non-hemorrhagic stroke patients were selected using purposive sampling. Data were collected through questionnaires and medical records, and analyzed using the Chi-square test with a significance level of α = 0.05. Result: The results showed a significant relationship between history of cardiovascular disease (p = 0.024), and smoking habits (p = 0.031) with cognitive decline in non-hemorrhagic stroke patients. Meanwhile, age (p = 0.228), gender (p = 0.714), family history of stroke (p = 0.580), and hypertension (p = 0.995) were not statistically associated with cognitive decline. Conclusion: This study suggests the importance of early detection and management of associated risk factors, including preventive education for vulnerable age groups, regular control of cardiovascular conditions, and promotion of a healthy lifestyle free from smoking as a preventive effort against further cognitive decline